2022
DOI: 10.1103/physrevb.105.174404
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic materials based on transition-metal dichalcogenides: Potential platform for reversible control of Dzyaloshinskii-Moriya interaction and skyrmion via electric field

Abstract: Exploring novel two-dimensional multiferroic materials that can realize electricfield control of two-dimensional magnetism has become an emerging topic in spintronics. Using first-principles calculations, we demonstrate that non-metallic bilayer transition metal dichalcogenides (TMDs) can be an ideal platform for building multiferroics by intercalated magnetic atoms. Moreover, we unveil that with Co intercalated bilayer MoS 2 , Co(MoS 2 ) 2 , two energetic degenerate states with opposite chirality of Dzyaloshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Particularly, the family of Janus vdW magnets, which lacks inversion symmetry with different atoms occupying top and bottom layers, has been predicted to possess large enough DMI to generate skyrmions. Additionally, it has been shown that when an electric field is applied perpendicular to the CrI 3 monolayer, the DMI emerges due to the breaking of inversion symmetry . Another focus was designing full vdW heterostructures consisting of magnetic and nonmagnetic vdW layers, tuning the DMI through the proximity effect. , Moreover, metal FM/2D material interfaces are predicted to possess significant DMI with strong magnetocrystalline anisotropy energy (MAE). , The Néel-type magnetic skyrmions observed in Fe 3 GeTe 2 crystals were attributed to the DMI due to the oxidized interfaces . Ferroelectrically controllable skyrmions , have also been recently proposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the family of Janus vdW magnets, which lacks inversion symmetry with different atoms occupying top and bottom layers, has been predicted to possess large enough DMI to generate skyrmions. Additionally, it has been shown that when an electric field is applied perpendicular to the CrI 3 monolayer, the DMI emerges due to the breaking of inversion symmetry . Another focus was designing full vdW heterostructures consisting of magnetic and nonmagnetic vdW layers, tuning the DMI through the proximity effect. , Moreover, metal FM/2D material interfaces are predicted to possess significant DMI with strong magnetocrystalline anisotropy energy (MAE). , The Néel-type magnetic skyrmions observed in Fe 3 GeTe 2 crystals were attributed to the DMI due to the oxidized interfaces . Ferroelectrically controllable skyrmions , have also been recently proposed.…”
mentioning
confidence: 99%
“…33,34 Moreover, metal FM/2D material interfaces are predicted to possess significant DMI with strong magnetocrystalline anisotropy energy (MAE). 35,36 The Neél-type magnetic skyrmions observed in Fe 3 GeTe 2 crystals were attributed to the DMI due to the oxidized interfaces. 37 Ferroelectrically controllable skyrmions 38,39 have also been recently proposed.…”
mentioning
confidence: 99%
“…As illustrated in Figure 4 B, the opposite electric polarizations just correspond to the opposite chirality of DMI. 62 By sweeping an out-of-plane electric field, the sign of DMI parameter d changes synchronously with the electric polarization P switching, 63 as illustrated in Figure 4 C. At the same time, harnessing the electric field also causes the magnitude variations of anisotropy and exchange interactions, and so affects the SMT’s radius. Thus, because of the intrinsic magnetoelectric coupling in 2D multiferroics, the effective control of SMTs with tunable size and reversible chirality can be realized by applying electric field to control the electric polarization and DMI.…”
Section: Representative Modulation Approachesmentioning
confidence: 99%
“… 61 Considering the direction of magnetization in the skyrmion core (m), four energetically degenerate skyrmionic states with different direction combinations of P and m, can be switched between each other by applying external electric and magnetic fields. 61 This concept was predicted to be realized in various 2D multiferroic monolayers, such as CrN, 61 Co(MoS 2 ) 2 (bilayer MoS 2 with Co intercalated), 62 CuCrP 2 Se 6 and HgInP 2 O 6 . 63 Different from skyrmions in first three materials with the perpendicular magnetic anisotropy, HgInP 2 O 6 monolayer with the in-plane anisotropy possesses isolated asymmetrical bimerons.…”
Section: Representative Modulation Approachesmentioning
confidence: 99%
See 1 more Smart Citation